Epigrafi Indonesia Dalam Kerangka Pikir Pasca - Modernisme - Daud Aris Tanudirjo (Balai Arkeologi Yogyakarta, 1994)
The interest in studying inscriptions as a source of history in Indonesia has been ingrained since the beginning of the XIX century. This is evidenced by the publication of the book The History of Java in 1817. The author, Sir Thomas Stamford Raffles, the governor-general of England set aside two chapters of his book to discuss and classify several inscriptions, both in Old Javanese and Sanskrit. Even though Raffles' study cannot be called scientific, at least he has tried to give meaning to the traced remains that he knows. It can be said that Raffles was the first to make use of this written legacy to share the history of Java.